Management and Learning Practices in an Islamic School: A Case Study at MTS IRA Medan - Lubis, Yani; Aulia, Dinda Sabda; Hakim, Widiya Mentari; Alzahwa, Nayla (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research examines how educational management, school facilities, and learning practices are carried out at MTS Swasta IRA Medan, an Islamic junior high school overseen by the Ministry of Religious Affairs. Conducted as part of the Field Experience Program (PLP I) for English Education students, this qualitative descriptive study utilized observations and interviews to review the institution’s managerial system, infrastructure, and instructional procedures. The findings indicate that the school has implemented management approaches consistent with national education standards and the framework of School-Based Management. Its facilities and infrastructure generally support teaching and learning, though enhancements in laboratory resources and digital learning tools remain necessary. The adoption of the Merdeka Curriculum has begun through structured lesson plans, differentiated instruction, and character education grounded in Islamic values. Overall, the study concludes that MTS Swasta IRA Medan shows a strong dedication to improving educational quality and integrating Islamic principles, even though improvements are still needed in teacher capacity-building and the use of learning technologies.